Reduction of the Car Toxic Emissions by using Double Catalytic Converter - Othman Aljamal, Mohammed (Palestine Polytechnic University, 2017)
Exhaust gas pollutants emitted to the atmosphere are seriously considered to be hygienic and environmental risk. This project responds to environmental and humanity needs to reduce the concentration of the toxic emissions by using double Catalytic Converter. In order to achieve these goals, a new exhaust system was designed. The project Confirms the validity of modifying the exhaust system by using SolidWorks program. Experimental Results show that using double catalytic converter has a good effect in reducing the toxic emission, the estimated reduction percentage of these gases (without catalytic converters, after the first one and after the second one) as shown in following table
CD29363 , 2016
CD 29363 , no of pages 74, ميكانيك 4/2016 , in the store
Keywords: Reduction of the Car Toxic Emissions by using Double Catalytic Converter